2007
DOI: 10.1111/j.1523-5378.2007.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of NOD1 and IL-8, but not Polymorphisms of TLR4 Genes, Are Associated with Helicobacter pylori-Induced Duodenal Ulcer and Gastritis

Abstract: E266K CARD4/NOD1, but not the TLR4 gene polymorphism increases the risk of peptic ulceration in H. pylori-positive patients. The -251 IL-8 polymorphism was significantly associated with either gastritis or DU in H. pylori-infected subjects. Host factors including intracellular pathogen receptors and IL-8 production play an important role in H. pylori-induced gastric mucosal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 34 publications
4
60
1
1
Order By: Relevance
“…Gil et al found that M. pneumoniae colonised at a higher rate in patients with asthma (24.7%) than those without (5.7%), possibly inducing the wheezing events 39 . Qasem and colleagues, in a study of both asthmatic and non-asthmatic patients, found that M. pneumoniae was more common in asthmatic patients and was also related to the exacerbation of asthma symptoms (patients with suspected viral infections were excluded from this study) 38 . In a study conducted in France of children with known asthma and children with a new diagnosis of asthma, Biscardi et al found that M. pneumoniae and C. pneumoniae were found in both groups of children, but at higher infection rates in those children with newly diagnosed asthma (50% of newly diagnosed patients had M. pneumoniae infection compared with 5.2% of stable asthma patients).…”
Section: Asthma and Other Microorganismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gil et al found that M. pneumoniae colonised at a higher rate in patients with asthma (24.7%) than those without (5.7%), possibly inducing the wheezing events 39 . Qasem and colleagues, in a study of both asthmatic and non-asthmatic patients, found that M. pneumoniae was more common in asthmatic patients and was also related to the exacerbation of asthma symptoms (patients with suspected viral infections were excluded from this study) 38 . In a study conducted in France of children with known asthma and children with a new diagnosis of asthma, Biscardi et al found that M. pneumoniae and C. pneumoniae were found in both groups of children, but at higher infection rates in those children with newly diagnosed asthma (50% of newly diagnosed patients had M. pneumoniae infection compared with 5.2% of stable asthma patients).…”
Section: Asthma and Other Microorganismsmentioning
confidence: 99%
“…EBV infection is also associated with a number of non-Hodgkin's lymphomas (NHL), including Burkitt lymphoma (BL) and diffuse large B cell lymphoma (DLBCL) 38 . Although rare in Australia, EBVassociated BL is endemic in regions of Africa and Papua New Guinea 22 .…”
Section: Ebv-associated Hodgkin and Non-hodgkin Lymphomasmentioning
confidence: 99%
See 2 more Smart Citations
“…HP and inflammatory infiltrates start to produce oxidative stress in gastric microenvironment. HP-NAP stimulates (nicotinamide adenine dinucleotide) oxidase assembly and production of reactive oxygen species [41]. Neutrophils express the myeloperoxidase enzyme, which produces a powerful oxidant hypochlorous anion (OCl − ) from H 2 O 2 in the existence of Cl − .…”
Section: Al-ezzymentioning
confidence: 99%